Pulmonary Artery Thromboembolism (PATE) in Paediatrics: Three Clinical Case Presentations - Asipauskaitė, Gabija; Miškinaitė, Greta; Dagys, Algirdas; Gurskis, Vaidotas (Acta medica Lituanica, 2026)
Background: Pulmonary artery thromboembolism in children is an exceptionally rare condition. Because its clinical presentation and associated risk factors differ from those observed in adults, the condition is frequently underdiagnosed.Case description: We present three cases of paediatric pulmonary artery thromboembolism, each with distinct clinical presentations and differing risk factors. The first case involved a 15-year-old boy who developed fatal massive bilateral pulmonary artery thromboembolism after having spinal trauma, surgery, immobility, and central venous catheter placement. The second case concerned a 17-year-old girl with Prader–Willi syndrome and multiple comorbidities, who presented with severe respiratory failure and laboratory evidence suggesting pulmonary thromboembolism, although imaging to confirm the diagnosis was limited. The third case involved a previously healthy 17-year-old boy with upper-extremity deep venous thrombosis and confirmed pulmonary artery thromboembolism despite the absence of identifiable provoking factors.Conclusions: These cases illustrate the heterogeneity of paediatric PATE presentation, the variability of underlying risk factors, and the diagnostic challenges encountered in clinical practice, underscoring the need for heightened awareness among clinicians.
Keywords: Pulmonary embolism; pulmonary artery thromboembolism; paediatrics; children